Virtual reality technology improves the gait and balance function of the elderly: a meta-analysis of randomized controlled trials - Junyu Chen; Shuxia Yan; Haiyan Yin; Dan Lin; Ziqi Mei; Zichun Ding; Meng Wang; Yamei Bai; Guihua Xu (Archives of Medical Science)
Introduction Improving the gait and balance function is an important part of the health of the elderly. This study aimed to conduct a meta-analysis to evaluate the effects of virtual reality (VR) technology on the gait and balance function of the elderly.